RELATIONSHIP OF ATTITUDE OF CLASS IX STUDENTS 'DIET WITH BODY IMAGE SATISFACTION LEVEL AT SMPN 1 GUNUNG PUTRI 2018: HUBUNGAN SIKAP DIET SISWI KELAS IX DENGAN TINGKAT KEPUASAN BODY IMAGE DI SMPN 1 GUNUNG PUTRI TAHUN 2018 - Dewi Dewi Nopitasari; Rizka Rizka Sulistianingsih (Jurnal Ilmiah Wijaya, 2018)
Based on the results of preliminary studies which in conducted by researchers to 10 respondens it was found that 5 female stundents said they were dissatisfied because of overweight so there was a desire to go on a diet or trying to loss their weight, and 3 female students said they were dissatisfied with their current weight because they fet less weight or thin so they wanted to gain weight, while the other 2 female students said that their body weight was ideal and they wer satisfied with the bodyimage.The purpose of this study was to determine the relationship between dietary of 9thgrade students the statisfaction level of body image in Gunung Putri Junior High School In Bogor In 2018. The type of research was conducted by descriptive correlation with analytical survey design with cross sectional approach. This research wasconducted at Taruna Andigha Junior High School In Bogor. Sampling in this study used a total sampling technique. Data collection is obtained through a questionnaire. Data analysis that be used was univariate analysis and bivariateanalysis.Based on results of the research from 28 respondens, there wre 18 respondents were satisfied with a positive satisfaction level, 16 respondents and a negative level of satisfaction of 2 respondens that statistical test values is p=0,000 which means that P value 0,05, so Ho was rejected, Ha was accepted so that there was a relationship between dietary of grade 9 students with bodyimage satisfaction in Gunung Putri in 2018. From the calculation OR there are 9.000, dietary has an opportunity for the body image statisfaction level.For educational institutions to provide information on knowledge or bring health agencies to provide counseling to female students so the students are not wrong to go on a diet. And for respondents to take a dietary by the rules that do not harm them selves.